KAJIAN IMPLEMENTASI PERATURAN WALIKOTA NOMOR 34 TAHUN 2017 TENTANG PEDOMAN PENGELOLAAN PENGADUAN MASYARAKAT DI KOTA SEMARANG - Syafriyan Fais; puji - astuti; Nunik Retno Herawati; Lusia Astrika (Journal of Politic and Government Studies, 2018)
ABSTRACTIONThis study aims to analyze the implementation of Mayor Regulation No. 34 of 2017 which has been implemented since mid-2017 until now and the extent to which the implementation can achieve the established goal of realizing the management of public complaints to be more coordinated and provide access to the community to participate actively in submit complaintsType of research used in this research is analytical descriptive research type through qualitative approach. Sources of data used in the form of primary data derived from the results of in-depth interviews of research informants and secondary data in the form of archives and documentation. The technique of selecting informants using purposive sampling.The results of the study found that in the implementation of this Mayor Regulation is effective in increasing the active participation of Semarang City community participation in 2017 in conveying complaints due to the massive socialization conducted by the Semarang City Government. Sources of input reports from the public most use the means of complaints via SMS, Twitter and Web laporhendi. Types of categories of complaints are classified into 3 types of mild, moderate and severe reports after passing the verification and clarification stage of P3M before the report is disposed to the integrated OPD. While some of the obstacles are if there are reports of public complaints involving many WSS and are not included in the planning and budget of the year, and there are still procedures for handling different OPDs.The recommendation that the author gives to the Complaints Management in Semarang City is that Each response answer from the OPD needs to include contact person who can be contacted to facilitate the community who want to ask more questions related to the problem and displays additional image features on the system before and after the results of reporting through images to make it more credible. Keywords: Community Complaints Management, Policy, Implementation.